Interleukin-13 Propagates Prothrombin Kringle-2-Induced Neurotoxicity in Hippocampi In Vivo via Oxidative Stress - Jeong, Jae Yeong (Int J Mol Sci, 2021)
The present study investigated expression of endogenous interleukin-13 (IL-13) and its possible function in the hippocampus of prothrombin kringle-2 (pKr-2)-lesioned rats. Here we report that intrahippocampal injection of pKr-2 revealed a significant loss of NeuN-immunopositive (NeuN(+)) and Nissl(+) cells in the hippocampus at 7 days after pKr-2. In parallel, pKr-2 increased IL-13 levels, which reached a peak at 3 days post pKr-2 and sustained up to 7 days post pKr-2. IL-13 immunoreactivity was seen exclusively in activated microglia/macrophages and neutrophils, but not in neurons or astrocytes. In experiments designed to explore the involvement of IL-13 in neurodegeneration, IL-13 neutralizing antibody (IL-13Nab) significantly increased survival of NeuN(+) and Nissl(+) cells. Accompanying neuroprotection, immunohistochemical analysis indicated that IL-13Nab inhibited pKr-2-induced expression of inducible nitric oxide synthase and myeloperoxidase within activated microglia/macrophages and neutrophils, possibly resulting in attenuation of reactive oxygen species (ROS) generation and oxidative damage of DNA and protein. The current findings suggest that the endogenous IL-13 expressed in pKr-2 activated microglia/macrophages and neutrophils might be harmful to hippocampal neurons via oxidative stress.